Carbon gas fluxes from boreal aquatic sediments - Bergström, Irina (Finnish Environment Institute, 2013)
The carbon dioxide (CO2) and methane (CH4) fluxes from aquatic sediments have recently received considerable interest because of the role of these gases in enhancing climate warming. CO2 is the main end product of aerobic respiration and CH4 is produced in large amounts under anaerobic conditions. Shallow, vegetated sediments are an important source of both gases. CH4 may be transported via rhizomes and aerenchymal tissues of aquatic plants from the sediment to the atmosphere, thus avoiding oxidation in the aerated sediment surface and water column. Temperature is known to be a key factor affecting benthic CO2 and CH4 flux rates, but the interplay between other factors that may affect the fluxes from sediments is still poorly known. In order to study the spatial and temporal variability of carbon gas fluxes in boreal aquatic sediments, the area-based CO2 production rates in lake and brackish water sediments and CH4 emissions in vegetated lake littorals were measured in this work. The effects of temperature, sediment quality, plant species, zoobenthos and seasonal variation on flux rates were also estimated. The range of CO2 production rates measured in the field was 0.1–12.0 mg C m–2 h–1 and that of CH4 emission rates 0–14.3 mg C m–2 h–1. When incubated at elevated temperatures (up to 30 °C) in the laboratory, the CO2 production rates increased up to 70 mg C m–2 h–1. Temperature explained 70–94% of the temporal variation in the CO2 production in lake sites and 51% in a brackish water site. In the lake mesocosm, temperature explained 50–90% of the variation of CH4 emission. By contrast, CH4 oxidation rate was not dependent on temperature. The CH4 fluxes through the plants of six emergent and floating-leaved plant species were studied in the field (temperature range 20.4–24.9 °C). Stands of the emergent macrophyte Phragmites australis emitted the largest amounts of CH4 (mean emission 13.9 ± 4.0 (SD) mg C m-2 h–1), the mean emission rate being correlated with mean net primary production (NPP) and mean solar ...